The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1155/2018/1678385
|View full text |Cite
|
Sign up to set email alerts
|

Modelling and Simulation of the Radiant Field in an Annular Heterogeneous Photoreactor Using a Four-Flux Model

Abstract: This work focuses on modeling and simulating the absorption and scattering of radiation in a photocatalytic annular reactor. To achieve so, a model based on four fluxes (FFM) of radiation in cylindrical coordinates to describe the radiant field is assessed. This model allows calculating the local volumetric rate energy absorption (LVREA) profiles when the reaction space of the reactors is not a thin film. The obtained results were compared to radiation experimental data from other authors and with the results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The DOM method transforms the RTE into a simplified system of algebraic equations able to describe the photons' transport. The system may be solved along the direction of propagation, starting from the imposed boundary conditions 27 . This method has been used to model the photons' transport in a variety of reactor configurations, such as slurry, 105 flat plate, 41 packed bed, 40 optical fibers, 106 monoliths, 107 and immobilized annular 49 reactors.…”
Section: Photoreactor Model Development: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The DOM method transforms the RTE into a simplified system of algebraic equations able to describe the photons' transport. The system may be solved along the direction of propagation, starting from the imposed boundary conditions 27 . This method has been used to model the photons' transport in a variety of reactor configurations, such as slurry, 105 flat plate, 41 packed bed, 40 optical fibers, 106 monoliths, 107 and immobilized annular 49 reactors.…”
Section: Photoreactor Model Development: Governing Equationsmentioning
confidence: 99%
“…The scale‐up of a photoreactor requires the development of a mathematical model that is the enclosure of different sub‐models:12,25 the radiation emission model, the radiation absorption‐scattering model, the kinetic model, and the fluid‐dynamic model 26 . These sub‐models, when strongly interlinked, result in a complex system of integral‐differential equations that require numerical solutions 27 . Generally, the photocatalytic reaction rate is a function of the local volumetric rate energy absorption (LVREA), which is defined as the energy required to photons being absorbed per time and volume inside the photoreactor.…”
Section: Introductionmentioning
confidence: 99%
“…The discrete ordinates method (DOM) consists of transforming the RTE differential-integral form into a system of algebraic equations that can be solved by a computer (Jensen et al, 2007). This system of equations describes the transport of photons in a way that can be solved following the direction of propagation, starting from the values provided by the boundary conditions (Alvarado-Rolon et al, 2018). This method solves the RTE for a finite number of discrete solid angles, each associated with a vector direction (Casado et al, 2017a).…”
Section: Radiation Transport Modelingmentioning
confidence: 99%
“…The (Cambié et al, 2017)] and (ii) incident radiation flux under FSI and BSI mechanisms [reproduced from (Passalía et al, 2020)]. ability of this model to provide more accurate results for problems with a radiation field coupled with a chemical reaction has made it widely applied for photochemical application (Coelho, 2014;Alvarado-Rolon et al, 2018;Moreno et al, 2019;Lira et al, 2020;Peralta Muniz Moreira and Li Puma, 2021). For example, Passalía et al (2020) simulated an array of 18 LEDs to light a milli-reactor known as NETmix employing a DOM method, and they used the oxidation of trivalent arsenate to pentavalent arsenate in aqueous solutions as a reaction model [Figure 3 (ii)].…”
Section: Radiation Transport Modelingmentioning
confidence: 99%
“…These observations agree with the prior simulation and experimental work. 42 In the fluidized bed with a bed expansion height of H b = 40.2 mm and average solid fraction, ε s = 0.26, the radiation intensity attenuates highly in the solid photocatalyst particles, where the attenuation degree is a function of the solid concentration. Therefore, it can be concluded that the CO 2 photoreduction reaction mainly occurs in the thin area next to the inner wall.…”
Section: Simulation Theorymentioning
confidence: 99%